Empowering communities through archaeology and heritage : the role of local governance in economic development - Gould, Peter G. (London ; New York : Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2018)
"Peter G. Gould seeks to identify the essential success factors associated with a growing practice in archaeology: the sponsorship by archaeologists or heritage managers of local projects such as museums, tourism businesses, crafts cooperatives and similar activities within communities adjacent to archaeological or heritage sites. Typically, these are small projects intended to support economic advance in small communities. Rarely are they reported on in scholarly papers and, until now, they have never been subjected to study grounded in economic theory and practice. This is an area of study and analysis that is too important to lack suitable academic attention. This book argues that an essential factor in the success of community projects relates to the mechanisms used to govern the projects at the local level, and provides a much-needed systematical evaluation of the issues surrounding such governance. Drawing together theoretical insights from economics, political science, tourism scholarship, complexity scholarship, and non-profit best practices, it presents a model for community governance structures and illustrates the workings of that model through the four case studies. Armed with this book, practitioners will have both a theoretical foundation and practical approaches to consider when designing community projects"--
Archaeology and community economic development -- The public good paradigm and disempowered communities -- Governance alternatives -- Asociacion Inkallaqta : an artisans' cooperative in Peru -- Maya Centre women's group : a community business in Belize -- The Burren Centre : a heritage interpretive center in Ireland -- I Parchi della Val di Cornia : a cluster of heritage sites in Italy.
Includes bibliographical references (pages 157-178) and index.
Keywords: Community archaeology; Archaeology -- Economic aspects; Archaeology -- Social aspects; Cultural property -- Social aspects; Community development